How We Work Now: Preliminary Review of a Pediatric Neuropsychology Hybrid Model in the Era of COVID-19 and Beyond. (28th May 2021) - Lichtenstein, Jonathan D; Amato, Jennifer T; Holding, Emily Z; Grodner, Kelsey D; Pollock, Erica N; Marschall, Kelsea P; Scull, Sara
Abstract: Objective: Although telehealth has become a central component of medical care in response to the coronavirus disease 2019 (COVID-19) pandemic, comprehensive pediatric neuropsychological assessment over virtual platforms lacks empirical efficacy. This paper presents: a) the results of a quality improvement project examining the feasibility of in-person evaluation in the context of safety measures that alter test standardization, b) the impact such changes had upon neuropsychological test scores, and c) how using a hybrid model of clinical service delivery affected access to care. Method: We compared demographic and outcome variables between patients seen during the pandemic ( N  = 87) to a group of patients seen in our service immediately prior to COVID-19 ( N  = 87). A subset of those patients were case-matched for age and diagnosis ( N  = 39 per group). Children seen for neuropsychological re-evaluation during the pandemic ( N  = 10) were examined using pairwise comparison. Results: Groups did not differ on age, sex, or FSIQ. Despite changes to standardized administration, no group differences were found for any selected neuropsychological test variables in the larger sample or subsamples. In fact, all variables were moderately to highly correlated in the re-evaluation subgroup. The hybrid model expedited feedback sessions and increased face-to-face (telehealth) feedbacks. Conclusions: A hybrid model incorporating modified in-person testing and intake and feedback encounters via telehealth may be a feasible and effective way to provide pediatric neuropsychological services. These preliminary findings suggest such novel aspects of neuropsychological evaluation could represent an improvement over pre-COVID models, especially in rural settings.